2022
DOI: 10.1002/lom3.10495
|View full text |Cite
|
Sign up to set email alerts
|

Testing the usefulness of optical data for zooplankton long‐term monitoring: Taxonomic composition, abundance, biomass, and size spectra from ZooScan image analysis

Abstract: The pelagic ecosystem of the Arctic Ocean is threatened by severe changes such as the reduction in sea‐ice coverage and increased inflow of warmer Atlantic water. The latter is already altering the zooplankton community, highlighting the need for monitoring studies. It is therefore essential to accelerate the taxonomic identification to speed up sample analysis, and to expand the analysis to biomass and size assessments, providing data for modeling efforts. Our case study in Fram Strait illustrates that image‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 94 publications
1
8
0
1
Order By: Relevance
“…This suggests that both approaches offer extensive capabilities for elucidating zooplankton compositions, particularly regarding the ratio of copepods to cladocerans which can often be an important zooplankton community characteristic in terms of food quality of zooplankton for fish [44]. The high number of samples that can be processed in comparison to classical microscopic counting and identification allows a much higher temporal and spatial resolution of analyses of zooplankton dynamics in lakes [18,30]. Such a better temporal and spatial resolution can offer more detailed insights into pelagic ecosystem processes highly relevant for lake and fisheries management [5,45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that both approaches offer extensive capabilities for elucidating zooplankton compositions, particularly regarding the ratio of copepods to cladocerans which can often be an important zooplankton community characteristic in terms of food quality of zooplankton for fish [44]. The high number of samples that can be processed in comparison to classical microscopic counting and identification allows a much higher temporal and spatial resolution of analyses of zooplankton dynamics in lakes [18,30]. Such a better temporal and spatial resolution can offer more detailed insights into pelagic ecosystem processes highly relevant for lake and fisheries management [5,45].…”
Section: Discussionmentioning
confidence: 99%
“…Of course, the quality of the analysis depends on the optical resolution. Several studies have shown that optical detection methods provide results comparable to traditional microscopic analysis [29,30]. Sample volumes that have traditionally been manually assessed in counting chambers under a binocular or microscope can now be digitized and captured for analysis simultaneously using modern technology.…”
Section: Introductionmentioning
confidence: 99%
“…In the Lima estuary, L1 and L2 were located in the lower estuary; L3 was located in the middle estuary; and L4 and L5 were located in the upper estuary. Zooplankton and MPs in estuarine water were collected by means of a 150 µm mesh size planktonic net (in general, the standard size regarding zooplankton sampling is a mesh size between 150 and 200 µm [39,40]). At each sampling site, planktonic tows were performed for 1 min near the surface of the water.…”
Section: Sampling Methodologymentioning
confidence: 99%
“…Nadeel hiervan is de lage taxonomische resolutie, vergelijkbaar met in situ plankton imaging. De organismen op ZooScan beelden kunnen ook worden opgemeten en de ZooScan kan daarom ook gebruikt worden voor bepalen van parameters als grootteverdeling en biomassa met vergelijkbare resultaten als directe metingen (Cornils et al 2022).…”
Section: Netbemonsteringunclassified